Gereja dan Misi Menurut Perspektif Lesslie Newbigin dan Johan Herman Bavinck - Doni Herwanto Harianja (STTRII, 2023)
This article explains how the ‘nature of the church, which is mission’ affects the activities of the church and the continuity of church life in the world. This goal is achieved by using a descriptive-comparative method, through an analysis and comparison of the thoughts of Lesslie Newbigin and Johan Herman Bavinck regarding the church and mission. This article shows that the activity and continuity of church life are closely related to church identity.